The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/joitmc7040245
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Learning Orientation and Business Model Innovation on Entrepreneurial Performance: Focused on South Korean Start-Up Companies

Abstract: The purpose of this study is to empirically confirm the importance of learning orientation in the operation of start-up companies. In the literature, it is well known that this learning orientation plays a big role in improving the performance of start-ups by cultivating organizational members’ capabilities in detail, encouraging active learning, and creating new knowledge. To this end, a business model innovation framework for start-ups was established by empirically validating the theoretical research model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
4
0
1
Order By: Relevance
“…Overall, the discussions highlighted the significance of mindset change programs, regular trainings, internship programs, effective incubation practices, and strong mentorship and coaching programs for the creation and development of an incubation and innovation prototype. The findings are supported by previous studies such as (Bae & Choi, 2021;Li, Ahmed, Qalati, Khan, & Naz, 2020;Lyken-Segosebe, Montshiwa, Kenewang, & Mogotsi, 2020). In respect to the abovementioned discussions, some of the respondents were quoted as follows;…”
Section: Availability Of Internship Programmessupporting
confidence: 81%
“…Overall, the discussions highlighted the significance of mindset change programs, regular trainings, internship programs, effective incubation practices, and strong mentorship and coaching programs for the creation and development of an incubation and innovation prototype. The findings are supported by previous studies such as (Bae & Choi, 2021;Li, Ahmed, Qalati, Khan, & Naz, 2020;Lyken-Segosebe, Montshiwa, Kenewang, & Mogotsi, 2020). In respect to the abovementioned discussions, some of the respondents were quoted as follows;…”
Section: Availability Of Internship Programmessupporting
confidence: 81%
“…The sub-factors of entrepreneurial orientation are innovativeness, risk-taking and proactiveness, and although they exist independently, they are linked to each other and affect each other, and one dimension alone is insufficient to explain the concept of corporate orientation (Miller, 1983; Wiklund & Shepherd, 2005). Since several dimensions interact to determine the level of entrepreneurial orientation, many studies have identified entrepreneurial orientation as a single concept composed of innovativeness, risk-taking and proactiveness (Bae & Choi, 2021; Cowden & Tang, 2022; Riviezzo et al, 2019; Song et al, 2017).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Perusahaan harus memperkuat orientasi pembelajaran yang penting bagi entitas untuk menciptakan dan mencapai kinerja yang unggul (Zayed & Alawad, 2017). Orientasi pembelajaran mempengaruhi kinerja bisnis, hal ini menunjukkan bahwa kita perlu memupuk kemampuan anggota organisasi, secara aktif mendorong pembelajaran, dan berusaha menciptakan pengetahuan baru (Bae & Choi, 2021).…”
Section: Pendahuluanunclassified